CAR FREE DAY SEBAGAI ALTERNATIF WISATA EDUKASI BAGI KELUARGA DI KOTA PADANG - Lili Dasa Putri (IKIP Siliwangi Bandung, 2021)
Boredom from work and routines carried out by children, adults, and parents alike need a container that makes them fresh. Many things can be done to restore the spirit and make you refreshed, starting from sports, recreation and others. Currently car free days in several cities are rife in Indonesia, both small cities and big cities. There are many things that can be done and enjoyed during the car free day and can be enjoyed by all ages. Car free day as a form of educational tourism which presents a lot of educational content directly or indirectly. In addition, on the car free day, visitors can also enjoy a variety of local, national and even international culinary delights. Apart from being able to refresh on a car free day, you can also get daily necessities, because there are many sellers we meet there and sell various types of goods. Care free day deserves to be an alternative educational tourism for families.